New concepts for cybersecurity in port communication networks - Nils Meyer-Larsen; Rainer Müller; Katja Zedel (Artificial Intelligence and Digital Transformation in Supply Chain Management: Innovative Approaches for Supply Chains. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 27, 2019)
Purpose: Seaports are to a growing extent controlled by IT systems. Smooth information exchange is crucial for business. Downtimes give rise to substantial financial losses and supply bottlenecks, due to the interconnections in a complex alliance of port stakeholders' systems. Hence, Cyber security in an important aspect in Port Communication Systems. Methodology: The project SecProPort will develop a holistic IT security architecture for port communication networks, which will support the security requirements of the stakeholders' operating procedures, protect them against sabotage, and prevent third parties from illicitly gathering sensitive data or getting unauthorized access to the communications network. Findings: The desired architecture is to be implemented by first analyzing typical attack scenarios targeted at the data processed in the port communication alliance. The next step entails designing the actual security architecture for the alliance and installing a prototype in collaboration with the application partners. Originality: SecProPort aims at a holistic approach with respect to secure port communications networks, rather than addressing individual stakeholders. The architecture will also provide resilience measures for minimizing the impact on other actors in the alliance in case of an incident, and returning to normal operation in a controlled manner.
urn:nbn:de:gbv:830-882.054507; 10419/209196; https://econpapers.repec.org/RePEc:zbw:hiclpr:27
Keywords: 650; Port communication network; Maritime cybersecurity; Port community system; Maritime blockchain